「しらせ」船上重力データの再処理 - 松崎, 和也; マツザキ, カズヤ; 福田, 洋一; フクダ, ヨウイチ; 野木, 義史; ノギ, ヨシフミ; Matsuzaki, Kazuy; Fukuda, Yoichi; Nogi, Yoshifumi (2014)
P(論文) 日本南極地域観測隊では「しらせ」船上での重力測定を実施しているが，重力計のドリフトやオフセットにばらつきがあることから，小西ほか（2006）では，第46次隊までのデータについて，衛星高度計データによる海域重力モデルを基準とした補正が行われている．しかし，それ以降の取得データは未補正であり，また，衛星高度計による海域重力モデルも新しくなっていることから，今回，第52次隊までのすべての船上重力データについて再処理を行った．具体的には，未処理だった第47次隊から第52次隊のデータに含まれる異常値を除去した後，第27次隊から第52次隊の全データについて，最近のモデルgrav.img.20.1を基準としてドリフトおよびオフセットの補正を行った．これらの処理の概要について報告するとともに，補正済みデータセットを利用したリュツォ・ホルム湾からアムンゼン湾沖にかけての地殻構造推定結果について述べる． To compile consistent data sets of Japanese Antarctic Research Expedition (JARE) shipborne gravity data, we applied drift and offset corrections to data sets obtained from JARE-27 to -52 by using a new satellite altimetric gravity model as the reference. Konishi et al. (2006) had previously conducted drift and offset corrections for data obtained up to and including JARE-46 so that the shipborne data fitted the satellite altimetric gravity data of grav.img.11.1 (Sandwell, 2004). Following the method of Konishi et al. (2006), we extracted gravity values from the altimetric gravity model of grav.img.20.1 (Sandwell, 2012) along the ship tracks, and then compared these values with those of the shipborne gravity data. These comparisons revealed large discrepancies near the turning points of the ship tracks, and large drifts and offsets in some of the data sets. We removed data that contained large discrepancies, and applied drift and offset corrections to the remaining data by assuming polynomial functions of time as the drift model. These reprocessed data sets were used for estimating crustal structure near Syowa Station. departmental bulletin paper